Piano Culture in 19th-Century Paris - Sala, Massimiliano (Turnhout Brepols, 2015)
The volume aims to investigate the world of the piano in France, and the evolution of the instrument between the ancien régime and the Restoration. Particular attention will be devoted to the circulation of central European pianists at the turn of the nineteenth century, their influence on the development of piano culture and technique and the impact this had on French musical tastes. Nineteen contributions will explore the piano industry, aspects of performance practice and the bravura tradition, and will investigate certain lines of interaction between publishers, composers, institutions and concert venues between the French Revolution and the first Industrial Revolution. The ultimate aim will be to determine more comprehensively the role of piano culture within nineteenth-century Parisian musical life.Table of ContentsPrefaceOverviewLeon Plantinga, Paris after Napoleon: Hub for Europes PianistsPublishing and the Piano IndustryDavid Rowland, Pianists and the European Music Trade c1790-1820 Henri Vanhulst, Le concerto pour piano dans les catalogues des éditeurs parisiens et lyonnais jusquaux environs de 1820 Cécile Reynaud, Les éditeurs français de Carl Czerny. Essai de chronologie des éditions des oeuvres de Czerny en France (1825-1830) Herbert Seifert, Musical and Biographical Information in Some Letters from and to the Composer and Publisher Ignaz Pleyel Pierre Goy, Le développement du jeu «moderne» du piano entre 1820 et 1830: Les changements dans la facture instrumentale et le développement de nouveaux moyens pianistiqueCentral European Composers and the Development of Piano VirtuosityAlban Ramaut, Antoine Reicha et le concept de virtuosité: approche étymologique dun mot à la frontière de deux siècles Alicia C. Levin, «A Musician of the First Order»: Frédéric Kalkbrenners Virtuoso Strategies for Paris Rohan H. Stewart-MacDonald, The Second Solo in the Opening Movements of Early-Romantic Parisian Piano Concertos: Frédéric Kalkbrenner (1785-1849) and His Contemporaries Christian Ahrens, A Real Symphonie Concertante in Pleyels Manner: Johann Nepomuk Hummels (Double) Concerto for Piano and Violin Op. 17Jan Ladislav DussekMichaela Freemanová, Jan Ladislav Dussek and His First Biographers Frédéric de La Grandville, Dusseks Reception as a Musician at the Paris Music Conservatoire, 1807-1812 Richard Fuller, A Musical 'Wertheriade' (?) The Particular and Unique Character of Dusseks Piano Concerto in G minor, Op. 49/50Performing Style and DidaticsStephanie Frakes, 'Cantabile' in French Methods for Piano 1797-1840 J. Mackenzie Pierce, 'Ersatz Improvisation': Chopins Opus 28 and the Published Prelude Collection Fiorella Sassanelli, Scelte musicali e repertori degli allievi pianisti del Conservatoire di Parigi: gli exercices des élèves (1800-1824) e il 'morceau de lecture à vue' del 1829Reception of Piano Music and VirtuososShaena B. Weitz, 'Le Pianiste' and Its History of Pianism in Paris: «The Corneilles and Racines of piano are not 'perruques'!» Majella Boland, Contrasts in John Field Reception: The Parisian Images Yael Bitrán, Henri Herz and His Mexican Biography: A Response from a VirtuosoBiographies Index of Names
Keywords: 19th Century (1801-1900); Piano; Paris (France)